Darden ends long career - Ladd, Joan (Raton Range Raton, New Mexico, 1980)
Newspaper Article on William H. Darden's retirement from assistant district attorney.
Master list item #: 1
File location is in the Raton File Cabinet
Keywords: Darden, William H; Wright, John; Reynolds, George; Hobbes, John; Caldwell, Joe; Lamb, Margaret; District Attorneys office; University of Colorado; Raton High School; National Guard; Gate City Building; Sugarite Canyon Board; Local History; Biography; Life and Customs; District Attorney; Retirement; Probate Judge; Bachlor's Law degree; World War II -- Army; Raton, New Mexico; Colfax County; Boulder, Colorado